PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Tissue-Resident Macrophage PIEZO1 Transduces Mechanical Stress into Inflammatory Pain in Acute Gout - Tianyi Shen; Ting Wang; Liyan Wu; Zihan Wang; Liqin Gan; Yubin Luo; Cong Liu; Yang Xu; De-An Guo; Qirui Bi; Wanying Wu; Lvyi Chen; et al. (Neuroscience Bulletin, 2026)

Projected seawater inundation induced by land subsidence will weaken the coastal carbon sink effect - Zhixiong Tang; Rongrong Ning; Fubin Luo; Shilei Peng; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; De Wang (CATENA, 2026)

Lycopene Attenuates Hexavalent Chromium–Induced Kidney Injury By Modulating PINK1/Parkin-Mediated Mitophagy - Quan-mei Zhang; Xia Zhang; Lun-Bin Xia; Kai Ge; De-Yong She; Shao-Shuai Bi (Biological Trace Element Research, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

Lycopene Attenuates Hexavalent Chromium-Induced Hepatotoxicity in Mice by Modulating the Nrf2 Signaling Pathway and the Unfolded Protein Response - Xia Zhang; Quan-mei Zhang; Lun-Bin Xia; Kai Ge; Milton Talukder; De-Yong She; Shao-Shuai Bi (Biological Trace Element Research, 2026)

Human activity intensifies land subsidence in the Yellow River Delta - Hui Xu; De Wang; Rongrong Ning; Xiaoyong Li; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; Yongwei Zhang (Estuarine, Coastal and Shelf Science, 2026)

Strategy for doubling the yield of phenolics in hydrothermal liquefaction of Arundo donax: mechanistic study on weak alkaline catalyst suppressing hydrochar formation and enriching phenolics in aqueous and biocrude phases - Lei-ming Bi; De-lin Fu; Xian-shuai Fu; Li-hui Zhang; Feng Duan (Biomass and Bioenergy, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

A novel and practical strategy for comprehensive differentiation and profiling of eight Curcumae varieties and their counterfeit from the Chinese market - Wenlong Wei; Saiyi Ye; Qiuyi Wen; Shuai Yao; Huiting Ou; Chunxiang Liu; Qirui Bi; Hua Qu; Erwei Hao; Chun Yao; Jianqing Zhang; De-an Guo (Food Chemistry, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

An experimental and kinetic modeling study on the ignition kinetics of a sustainable aviation fuel and its blends with a traditional RP-3 jet fuel - Quan-De Wang; Ping Zeng; Qian Yao; Jinhu Liang; Bi-Yao Wang; Fei Huang; Jian-Gang Liu; Zu-Xi Xia (Fuel, 2025)

The ABC1K gene family in Chinese cabbage: phylogeny, structure and function - Yuanxin Ye; Hengwu Ding; De Bi; Wen Ge; Jianke Yang; Shiyun Han; Sijia Zhang; Yuhong Liu; Xianzhao Kan (Genetic Resources and Crop Evolution, 2024)

Seismic activity characteristics of the Chinese continent based on a “hybrid” probability forecasting model - Yong Ma; Jin-Meng Bi; De-Miao Dong (Applied Geophysics, 2024)

Bio-derived modified halloysite nanotubes as eco-friendly flame retardants to endow epoxy with high thermal stability, mechanical performance and flame retardancy - Qing-Qing Bi; Ying-Ming Li; Lu He; De-Yi Wang (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pyrene-4,5,9,10-tetraone-based covalent organic framework/carbon nanotube composite as sodium-ion cathodes with high-rate capability - Lei Chen; Yuke Li; Yuemiao Zhang; Shi-Bin Ren; Jinhai Bi; Xinxian Xue; De-Man Han; Di Wu; Yujing Wang; Xianlang Chen; Yingpeng Wu (Chemical Engineering Journal, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Porous liquids assisted in-situ generated Co-LDH@MOF heterostructure with abundant defects for flame retardant and mechanical enhancement in polyurea composites - Kunpeng Song; Xue Bi; Dong Wang; Ye-Tang Pan; Meina Xie; Jiyu He; De-Yi Wang; Rongjie Yang (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Multifractal parameters reveal the impacts of shrub encroachment on soil particle size distribution (PSD) in a coastal wetland of the Yellow River Delta - Meifang Liu; De Wang; Xinpeng Tian; Yuru Wu; Xiaoli Bi (Journal of Coastal Conservation, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Accelerating precision feeding with the internet of things for livestock: From concept to implementation - Jiayi Su; Bi’e Tan; Zongyong Jiang; De Wu; C.M. Nyachoti; Sung Woo Kim; Yulong Yin; Jing Wang (Science Bulletin, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Estuarine groundwater level response to and recovery from extreme precipitation events: Typhoon Lekima in the Yellow River Delta - Fubin Luo; De Wang; Xinpeng Tian; Xiaoli Bi; Qian Zheng; Zixiang Zhou; Zhixiong Tang (Journal of Hydrology, 2024)

Dimensional change of red phosphorus into nanosheets by metal–organic frameworks with enhanced dispersion in flame retardant polyurea composites - Xue Bi; Kunpeng Song; Henglai Zhang; Ye-Tang Pan; Jiyu He; De-Yi Wang; Rongjie Yang (Chemical Engineering Journal, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Chemoreceptors from the commensal gut Roseburia rectibacter bind to mucin and trigger chemotaxis - Hong‐He Chen; Yu‐Xin Wang; De‐Feng Li; Chang Liu; Shuang‐Yu Bi; Cheng‐Ying Jiang; Shuang‐Jiang Liu (Environmental Microbiology, 2023)
Chemotaxis is crucial for bacterial adherence and colonization of the host gastrointestinal tract. Previous studies have demonstrated that chemotaxis affects the virulence of causative pathogens and the infection in the host. However, the chemotactic abilities of non‐pathogenic and commensal gut bacteria have rarely been explored. We observed that Roseburia rectibacter NSJ‐69 exhibited flagella‐dependent motility and chemotaxis to a variety of molecules, including mucin and propionate. A genome‐wide analysis revealed that NSJ‐69 has 28 putative chemoreceptors, 15 of which have periplasmic ligand‐binding domains (LBDs). These LBD‐coding genes were chemically synthesized and expressed heterologously in Escherichia coli . Intensive screening of ligands revealed four chemoreceptors bound to mucin and two bound to propionate. When expressed in Comamonas testosteroni or E. coli , these chemoreceptors elicited chemotaxis toward mucin and propionate. Hybrid chemoreceptors were constructed, and results showed that the chemotactic responses to mucin and propionate were dependent on the LBDs of R. rectibacter chemoreceptors. Our study identified and characterized R. rectibacter chemoreceptors. These results will facilitate further investigations on the involvement of microbial chemotaxis in host colonization.

The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China - Ziqing Li; Jianqing Zhang; Qian Meng; Lin Yang; Mingyang Qiu; Yun Li; Shuai Yao; Wenlong Wei; Changliang Yao; Qirui Bi; Jiayuan Li; De-an Guo (Food Research International, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Sustainable phytoextraction of metal-polluted agricultural land used for commercial photovoltaic power generation - Zhu Li; Xi Sun; Jiawen Zhou; Longhua Wu; De Bi; Jie Zhao; Renfeng Zhu; Peter Christie (Journal of Cleaner Production, 2023)

Occurrence and distribution of microplastics in coastal plain soils under three land-use types - De Bi; Beibei Wang; Zhu Li; Yabing Zhang; Xin Ke; Chengwang Huang; Wuxing Liu; Yongming Luo; Peter Christie; Longhua Wu (Science of The Total Environment, 2023)

Plastome evolution of Aeonium and Monanthes (Crassulaceae): insights into the variation of plastomic tRNAs, and the patterns of codon usage and aversion - Shiyun Han; De Bi; Ran Yi; Hengwu Ding; Longhua Wu; Xianzhao Kan (Planta, 2022)

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Auxin acts as a downstream signaling molecule involved in hydrogen sulfide-induced chilling tolerance in cucumber - Xiao-Wei Zhang; Feng-Jiao Liu; Jiang Zhai; Fu-De Li; Huan-Gai Bi; Xi-Zhen Ai (Planta, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Characterization of some African tropical heartwood lignins by 1D 13C and 1H-NMR: molecular structure and hydroxyl groups’ distribution - Rodrigue Safou Tchiama; Bikoro Bi Athomo Arsène; Péguy Starlin Engozogho Anris; Aristide Gervais Akagah; Bernard De Jeso (Journal of the Indian Academy of Wood Science, 2019)

Understanding the natural durability of some African tropical heartwoods toward Pycnoporus sanguineus and Antrodia sp.: lignin structure and cellulose morphology control - Rodrigue Safou Tchiama; Patrice Soulounganga; Péguy Starlin Engozogho Anris; Arsène Bikoro Bi Athomo; Timoléon Andzi Barhé; Bernard De Jeso; Bertrand Charrier; Aristide Gervais Akagah (Journal of the Indian Academy of Wood Science, 2018)

Physico-mechanical properties of particleboard made from seaweed adhesive and tapioca starch flour - Kang Chiang Liew; Peter Bi De Ting; Yu Feng Tan (Journal of the Indian Academy of Wood Science, 2018)

Forecasting industrial water demand in Huaihe River Basin due to environmental changes - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Shou-hai Bi; Amgad Elmahdi; Chuan-hua Liao; You-de Li (Mitigation and Adaptation Strategies for Global Change, 2018)

A first estimate of sea turtle bycatch in the industrial trawling fishery of Gabon - Paolo Casale; Gaspard Abitsi; Marie Pierre Aboro; Pierre Didier Agamboue; Laureen Agbode; Nontsé Lois Allela; Davy Angueko; Jean Noel Bibang Bi Nguema; François Boussamba; Floriane Cardiec; Emmanuel Chartrain; Claudio Ciofi; et al. (Biodiversity and Conservation, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Organic Solvent-Tolerant Marine Microorganisms as Catalysts for Kinetic Resolution of Cyclic β-Hydroxy Ketones - Bi -Shuang Chen; Hui Liu; Fayene Zeferino Ribeiro de Souza; Lan Liu (Marine Biotechnology, 2017)

Integrated Life Cycle Assessment and Life Cycle Cost Model for Comparing Plug‐in versus Wireless Charging for an Electric Bus System - Zicheng Bi; Robert De Kleine; Gregory A. Keoleian (Journal of Industrial Ecology, 2017)
Summary An integrated life cycle assessment and life cycle cost (LCC) model was developed to compare the life cycle performance of plug‐in charging versus wireless charging for an electric bus system. The model was based on a bus system simulation using existing transit bus routes in the Ann Arbor–Ypsilanti metro area in Michigan. The objective is to evaluate the LCCs for an all‐electric bus system utilizing either plug‐in or wireless charging and also compare these costs to both conventional pure diesel and hybrid bus systems. Despite a higher initial infrastructure investment for off‐board wireless chargers deployed across the service region, the wireless charging bus system has the lowest LCC of US$0.99 per bus‐kilometer among the four systems and has the potential to reduce use‐phase carbon emissions attributable to the lightweighting benefits of on‐board battery downsizing compared to plug‐in charging. Further uncertainty analysis and sensitivity analysis indicate that the unit price of battery pack and day or night electricity price are key parameters in differentiating the LCCs between plug‐in and wireless charging. Additionally, scenario analyses on battery recycling, carbon emission pricing, and discount rates were conducted to further analyze and compare their respective life cycle performance.

Prediction of Type II Toxin-Antitoxin Loci in Klebsiella pneumoniae Genome Sequences - Yi-Qing Wei; De-Xi Bi; Dong-Qing Wei; Hong-Yu Ou (Interdisciplinary Sciences: Computational Life Sciences, 2016)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Inheritance and relationship between key agronomic and quality traits in an interspecific cross between Coffea pseudozanguebariae Bridson and C. canephora Pierre - Doffou Sélastique Akaffou; Perla Hamon; Sylvie Doulbeau; Jules Keli; Hyacinthe Legnate; Claudine Campa; Serge Hamon; Alexandre de Kochko; Bi Irié Arsène Zoro (Tree Genetics & Genomes, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Studies on chemical constituents of the leaves of Smallantus sonchifolius (yacon): Structures of two new diterpenes - De-Qiang Dou; Fang Tian; Ying-Kun Qiu; Zheng Xiang; Bi Xia Xu; Ting Guo Kang; Feng Dong (Natural Product Research, 2010)

Comparative proteomic analysis of apomictic monosomic addition line of Beta corolliflora and Beta vulgaris L. in sugar beet - Hong Zhu; Ying-Dong Bi; Li-Jie Yu; De-Dong Guo; Bai-Chen Wang (Molecular Biology Reports, 2009)

Complex chromosome 17p rearrangements associated with low-copy repeats in two patients with congenital anomalies - L. E. L. M. Vissers; P. Stankiewicz; S. A. Yatsenko; E. Crawford; H. Creswick; V. K. Proud; B. B. A. de Vries; R. Pfundt; C. L. M. Marcelis; J. Zackowski; W. Bi; A. Geurts van Kessel; et al. (Human Genetics, 2007)

Production and analysis of transgenic wheat (Triticum aestivum L.) with improved insect resistance by the introduction of cowpea trypsin inhibitor gene - Rui-Ming Bi; Hai-Yan Jia; De-Shun Feng; Hong-Gang Wang (Euphytica, 2006)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

Effect of erythromycin on metabolism of quetiapine in Chinese suffering from schizophrenia - Kun-Yan Li; Xin Li; Ze-Neng Cheng; Bi-Kui Zhang; Wen-Xing Peng; Huan-De Li (European Journal of Clinical Pharmacology, 2005)